Optimization of Units Movement in Turn-Based Strategy Game - Kristo Radion Purba; Liliana Liliana; Johan Pranata (International Journal of Industrial Research and Applied Engineering, 2016)
Each game has an artificial intelligence that is used to fight the player, which will provide more challenge. But in some strategy games, unit movements are usually done using simple considerations. For example the rest of unit lives, unit strength, and so forth. In this study, a turn based strategy game is designed using genetic algorithm to control the movement of the enemy armies.In each turn, the enemy will move based on the potential level of produced damage to and from the opponent, the distance between the units, and the distance to the opponent’s building. The genetic algorithm’s chromosome for each unit contains the following information: the position where the unit will move, who is the target, and the distance to the armies’ centroid. Distance to centroid (midpoint) is used to force the units to remain in the set. The genetic algorithm process is used to control when and where the units will move or attack. From the test results, the genetic algorithm can create a more powerful enemy than the randomly moving enemy because it creates a higher winning chance of enemy units and acts more efficiently, in terms of the usage of money, the damage produced to the opponent, and the received damage.